THE INFLUENCE OF TRANSPARENCY, ACCOUNTABILITY, AND INTEGRITY ON EMPLOYEE PERFORMANCE AT THE REGIONAL REVENUE MANAGEMENT AGENCY OF JAYAPURA REGENCY, PAPUA PROVINCE - Thaime, Gracesela Karolina; Muspa, Muspa; Anshar, Muh. Ashary (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This study aims to analyze the influence of transparency, accountability, and integrity on employee performance at the Regional Revenue Management Agency of Jayapura Regency, Papua Province. The research is grounded in the importance of applying good governance principles to enhance the effectiveness and efficiency of employee performance, particularly within local government institutions that play a strategic role in managing regional revenue. This research uses a quantitative method with an associative approach. Data were collected through questionnaires distributed to a number of respondents who are employees of the agency. Data analysis was conducted using SPSS software. The population of this study consisted of all 63 employees of the Regional Revenue Management Agency of Jayapura Regency, Papua Province. The results of the study indicate that:(1) Transparency has a positive and significant effect on employee performance at the Regional Revenue Management Agency of Jayapura Regency;(2) Accountability has a positive and significant effect on employee performance at the same institution; (3) Integrity also has a positive and significant effect on employee performance.